The trouble with chickens : a J.J. Tully mystery - Cronin, Doreen; Cornell, Kevin (New York : Laura Geringer Books, 2011)
A hard-bitten former search-and-rescue dog helps solve a complicated missing chicken case.
Keywords: Dogs; Chickens; Humorous stories; Mystery and detective stories